2011
DOI: 10.1016/j.ptsp.2010.09.003
|View full text |Cite
|
Sign up to set email alerts
|

The influence of a balance training program on the electromyographic latency of the ankle musculature in subjects with no history of ankle injury

Abstract: a b s t r a c tBackground: Balance training is often employed for the prevention of ankle injuries. However, until now, most of the studies have focused on the prevention of a recurrent injury. The objective of this study was to look into the effects of balance training on the onset of peroneal muscle activity in healthy subjects. Methods: 34 participants (mean age ¼ 19.5 years AE 1.5; height ¼ 1.70 m AE 0.12; weight ¼ 62.06 kg AE 11.24), physically active, with no history of injuries took part in this study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 23 publications
(35 reference statements)
1
10
0
5
Order By: Relevance
“…However, some previous studies have reported that training utilizing unstable surfaces is not effective 10) .…”
Section: Discussionmentioning
confidence: 97%
“…However, some previous studies have reported that training utilizing unstable surfaces is not effective 10) .…”
Section: Discussionmentioning
confidence: 97%
“…Se siguieron las pautas de investigaciones previas en relación con programas de prevención en jugadores/as de baloncesto que utilizaron la propiocepción sobre platos de Böhler (ankle disk) o tablas de equilibrio similares como vía 8,13,15,18,19 . La duración completa del programa por sesión no conllevó un tiempo superior a 6-8 min para cada jugadora.…”
Section: Programa Preventivo De Propiocepción Sobre Platos De Böhlerunclassified
“…Sus resultados mostraron diferencias estadísticamente significativas entre grupos en lo relativo al control postural de la articulación. Por ello, fueron contundentes al asociar sus déficits a un mayor riesgo de recaídas y lo atribuyen, al igual que otras investigaciones 9,[12][13][14] , tanto al daño estructural de tipo articular, muscular y en las fibras nerviosas aferentes, como a la disrupción de los mecanorreceptores localizados en los ligamentos y cápsula articulares.…”
Section: Introductionunclassified
See 2 more Smart Citations